2019
DOI: 10.1177/0301006619874681
|View full text |Cite
|
Sign up to set email alerts
|

Typical Utilization of Gestalt Grouping Cues in Shape Perception by Persons with Autism Spectrum Disorder

Abstract: The common finding of better locally oriented perception among persons with autism spectrum disorder (ASD) is based on evidence from paradigms in which hierarchical stimuli are used to pit local and global processes against one another. However, in most cases, determining whether group differences reflect reduced global processing, enhanced local processing, or both is difficult. To provide more conclusive evidence for global perception in ASD, we examined shape formation and sensitivity to Gestalt heuristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This finding provides clear electrophysiologic evidence of disordered contour integration in children with ASD, extending beyond the preschool age cohort previously studied by Stroganova et al (2007) . Thus, despite several behavioral studies suggesting that children with ASD can accurately perceive ICs ( Milne and Scope, 2008 ; Hadad et al, 2019 ; Gowen et al, 2020 ), accumulating evidence points to clear differences in underlying neurophysiologic mechanisms that appear early in development and persist across childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding provides clear electrophysiologic evidence of disordered contour integration in children with ASD, extending beyond the preschool age cohort previously studied by Stroganova et al (2007) . Thus, despite several behavioral studies suggesting that children with ASD can accurately perceive ICs ( Milne and Scope, 2008 ; Hadad et al, 2019 ; Gowen et al, 2020 ), accumulating evidence points to clear differences in underlying neurophysiologic mechanisms that appear early in development and persist across childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, previous behavioral studies of IC perception in ASD children and adults have produced mixed results. Many have described no behavioral difference in closed contour integration in ASD relative to NT children or adults ( Milne and Scope, 2008 ; Hadad et al, 2019 ; Gowen et al, 2020 ). Yet, other studies have found ASD children exhibited lower performance than NT controls on tasks that required identification of illusory shapes ( Soroor et al, 2022 ), and lower accuracy along with longer reaction time in matching a solid shape with two illusory alternatives in the presence of local interference ( Nayar et al, 2017 ), implying a possible deficit in contour processing.…”
Section: Introductionmentioning
confidence: 99%
“…However, prior acquisition has been investigated under different time scales varying from short time frames to long‐term development and across different contexts. For example, different designs have been used to investigate prior acquisition in highly volatile environments with priors manipulated every few minutes (Lieder et al, 2019; Sapey‐Triomphe et al, 2021; Vishne et al, 2021), stable environnements (Pellicano & Burr, 2012), or priors acquired throughout life (e.g., perceptual illusions (Binur et al, 2022; Ganel & Goodale, 2003; Hadad, Russo, et al, 2019; Langer & Bülthoff, 2001; Sun & Perona, 1996)). It is likely that the process of learning and updating priors differs according to the time scale and context.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with prior literature, this electrophysiologic work points to deficits in feedback-supported contour integration in ASD (Knight EJ,Freedman EG,Myers EJ,Berruti AS,Oakes LA,Cao CZ,Molholm S and Foxe JJ, 2023;Stroganova TA et al, 2007) that are evident despite conflicting results behaviorally on whether IC processing deficits are present in autism. Some studies have found no difference between ASD and NT on behavioral measures of contour integration (Gowen E et al, 2020;Hadad BS et al, 2019;Milne E and Scope A, 2008), while other studies have described reduced accuracy and longer reaction times in these tasks (Nayar K et al, 2017;Soroor G et al, 2022). This discrepancy between behavioral and electrophysiologic investigation suggests that individuals with ASD may accomplish equivalent IC perception, albeit via different mechanisms than their NT counterparts.…”
Section: Feedforward and Feedback Connections Between Human Visual Co...mentioning
confidence: 99%